2022
DOI: 10.1021/acs.inorgchem.2c00769
|View full text |Cite
|
Sign up to set email alerts
|

Designing Optical Thermometers Using Down/Upconversion Ca14Al10Zn6O35: Ti4+, Eu3+/Yb3+, Er3+ Thermosensitive Phosphors

Abstract: Down/upconversion Ca14Al10Zn6O35 inorganic phosphors codoped with Ti4+/Eu3+ or Yb3+/Er3+ were prepared. The crystal structure and downconversion luminescence properties of Ca14Al10Zn6O35:Ti4+, Eu3+ phosphors were studied in detail. Ti4+ and Eu3+ occupied Al3+ and Ca2+ sites in the host lattice, respectively. Under the excitation of 273 nm, the emission peak in the 300–570 nm band originated from the 2T2 → O2– transition of Ti4+. The f–f transition of Eu3+ ions generated multiple peaks in the 570–800 nm range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Compared with the conventional contacted thermometers, a lot of attention has been attracted by luminescence thermometers, which utilize temperature-associated fluorescence characteristics, such as fluorescence intensity ratio (FIR), band position, decay time, full width at half-maximum of emission band, etc., of luminescent materials because of their advantages of rapid response, high accuracy/resolution, and contactless characteristic. , Particularly, by adopting the FIR technique, optical thermometry is extensively adopted, in which the temperature-related emission intensities of thermally coupled levels (TCLs) of rare-earth ions are investigated. , Fu et al revealed that the thermometric properties of rare-earth ions, which were based on their TCLs, can be adjusted by controlling the excitation wavelength and utilizing tridoping engineering. , However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity ( S r ) triggered by the small energy band gap of TCLs (200 ≤ Δ E ≤ 2000 cm –1 ). , For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ /Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ /Eu 3+ , with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing. Thereby, the utilization of the temperature-dependent FIR value of non-TCLs is a facile strategy to manipulate the thermometric behaviors of luminescent materials.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the conventional contacted thermometers, a lot of attention has been attracted by luminescence thermometers, which utilize temperature-associated fluorescence characteristics, such as fluorescence intensity ratio (FIR), band position, decay time, full width at half-maximum of emission band, etc., of luminescent materials because of their advantages of rapid response, high accuracy/resolution, and contactless characteristic. , Particularly, by adopting the FIR technique, optical thermometry is extensively adopted, in which the temperature-related emission intensities of thermally coupled levels (TCLs) of rare-earth ions are investigated. , Fu et al revealed that the thermometric properties of rare-earth ions, which were based on their TCLs, can be adjusted by controlling the excitation wavelength and utilizing tridoping engineering. , However, the optical thermometers based on the TCLs of rare-earth ions possess low relative sensitivity ( S r ) triggered by the small energy band gap of TCLs (200 ≤ Δ E ≤ 2000 cm –1 ). , For the purpose of addressing this issue, researchers proposed a new route, namely, using the FIR technique to deal with the temperature-dependent emission intensities of non-TCLs of luminescent compounds. To date, some compounds, such as BaTiO 3 :Er 3+ /Ho 3+ /Yb 3+ , La 3 Li 3 W 2 O 12 :Eu 3+ /Mn 4+ , Na 5 Y 9 F 32 :Ce 3+ /Tb 3+ , YVO 4 :Eu 3+ /Nd 3+ , LaGaO 3 :Cr 3+ /Nd 3+ , and Ca 14 Al 10 Zn 6 O 35 :Ti 4+ /Eu 3+ , with good thermometric properties, in which the non-TCLs are used, have been developed to realize contactless temperature sensing. Thereby, the utilization of the temperature-dependent FIR value of non-TCLs is a facile strategy to manipulate the thermometric behaviors of luminescent materials.…”
Section: Introductionmentioning
confidence: 99%